Building meaningful collaboration in conservation genetics and genomics - Robyn E. Shaw; Brittany Brockett; Jennifer C. Pierson; Stephen D. Sarre; Paula Doyle; Hannah B. Cliff; Mark D. B. Eldridge; Kimberly A. Miller; Kym Ottewell; Marissa L. Parrott; Maurizio Rossetto; Paul Sunnucks; et al. (Conservation Genetics, 2024)
Genetic diversity is the foundation of biodiversity, and preserving it is therefore fundamental to conservation practice. However, global conservation efforts face significant challenges integrating genetic and genomic approaches into applied management and policy. As collaborative partnerships are increasingly recognized as key components of successful conservation efforts, we explore their role and relevance in the Australian context, by engaging with key entities from across the conservation sector, including academia, botanic gardens, herbaria, seed banks, governmental/non-governmental organisations, private industry, museums, Traditional Owners, Indigenous rangers, and zoos and aquaria. By combining perspectives from these entities with comprehensive literature review, we identified five guiding principles for conservation genetic and genomic research and explored the different elements of, and approaches to, collaboration. Our reflections suggest that there is a substantial overlap in research interests across the Australian conservation sector, and our findings show that collaboration is increasing. We discuss approaches to building collaborative partnerships, the reciprocal benefits of collaborating, and some remaining challenges associated with data generation, data collection, and cross-cultural considerations. We emphasise the need for long-term national resourcing for sample and data storage and consistency in collecting, generating and reporting genetic data. While informed by the Australian experience, our goal is to support researchers and practitioners to foster meaningful collaborations that achieve measurable management outcomes in conservation genetics and genomics, both in Australia and globally.

First report of Bemisia tabaci MEAM1 (Hemiptera: Aleyrodidae) resistance to spirotetramat in Florida - Marcelo Dimase; Bruno Rossito De Marchi; Sriyanka Lahiri; Julien Beuzelin; Sam Hutton; Felipe Barreto da Silva; Hugh A. Smith (Crop Protection, 2024)

The effects of task instructions on pro and antisaccade performance - Alisdair J. G. Taylor; Sam B. Hutton (Experimental Brain Research, 2009)

Drug expectancy is necessary for stimulus control of human attention, instrumental drug-seeking behaviour and subjective pleasure - Lee Hogarth; Anthony Dickinson; Sam B. Hutton; Nieke Elbers; Theodora Duka (Psychopharmacology, 2006)